Microchip Capillary Electrophoresis Methods and Protocols - Henry, Charles.; Henry, Charles. (Methods in Molecular Biology, 2006)
Microchip capillary electrophoresis, a new and emerging technology that can rapidly analyze biological compounds as small as or smaller than a single cell, will have a major impact on biological sciences in the next 10 to 20 years. In Microchip Capillary Electrophoresis: Methods and Protocols, leading chemists and engineers concisely explain the principles behind this revolutionary technique and demonstrate its use in a variety of biochemical applications, ranging from the analysis of DNA, proteins, and peptides to single cell analysis and measuring the impact of surface modification on flow in microfluidic channels. The authors describe in detail the detection methods used, including mass spectrometry, electrochemistry, and conductivity. Since surface chemistry must be carefully considered for optimal operation at this scale, they also discuss methods of both adsorbed and covalent surface modification for its control. Fabrication methods for producing microchips with glass, poly(dimethylsiloxane), and other polymers are also provided so that even novices can produce simple devices for standard separations. The protocols follow the successful Methods in Molecular Biology™ series format, each offering step-by-step laboratory instructions, an introduction outlining the principles behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Instructive and well-detailed, Microchip Capillary Electrophoresis: Methods and Protocols provides a practical starting point for both initiating research in the field of microchip capillary electrophoresis and understanding the full range of how these new systems can be used successfully in biological research.